2010
DOI: 10.1097/prs.0b013e3181c722bb
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy for Nonhealing Cutaneous Wounds

Abstract: Summary Chronic wounds remain a major challenge in modern medicine and represent a significant burden, affecting not only physical and mental health, but also productivity, health care expenditure, and long-term morbidity. Even under optimal conditions, the healing process leads to fibrosis or scar. One promising solution, cell therapy, involves the transplantation of progenitor/stem cells to patients through local or systemic delivery, and offers a novel approach to many chronic diseases, including nonhealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 44 publications
(46 reference statements)
0
91
0
6
Order By: Relevance
“…Bone marrow-derived MSCs have been shown to be efficacious in the treatment of wounds, including chronic wounds [14,18,19]. Previous work in our laboratory has demonstrated that bone marrow-derived cells play an important role in cutaneous wound healing and that direct application of bone marrow-derived cells to patients with chronic nonhealing wounds leads to wound closure and dermal rebuilding [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow-derived MSCs have been shown to be efficacious in the treatment of wounds, including chronic wounds [14,18,19]. Previous work in our laboratory has demonstrated that bone marrow-derived cells play an important role in cutaneous wound healing and that direct application of bone marrow-derived cells to patients with chronic nonhealing wounds leads to wound closure and dermal rebuilding [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been shown to correct delayed wound healing in diabetic mice by promoting epithelialization, and augmenting angiogenesis and granulation tissue formation [13]. Furthermore, studies have shown that application of MSCs to nonhealing wounds can lead to increased angiogenesis and reduced scarring [14].…”
mentioning
confidence: 99%
“…Deep non-healing wounds that involve the full thickness of the skin and deeper structures (such as chronic wounds and burns) are among the greatest challenges to medicine. The incidence of nonhealing cutaneous wounds in the United States alone is 5 to 7 million cases per year, with an annual cost of over 20 billion dollars [32]. The effectiveness of treatment is estimated at 50%.…”
Section: Treatment Of Chronic Wounds and Burnsmentioning
confidence: 99%
“…65 MSCs act on wound healing through transdifferentiation or cell fusion to wound healing cells, 66 production of cytokines and GF, 67 maintenance of the extracellular matrix, modulation of the immune system, and wound contraction. 65,68 There is evidence that adipose-derived MSC and BM-MSC kept in culture for long time undergo spontaneous transformation and form tumors in vivo, which might jeopardize clinical application 69,70 (Table 1). On the other hand, MSC display immunosuppressive characteristics through interactions with Natural Killer cells, B and T lymphocytes, and monocytes, making them compatible for allogeneic transplantation, 71 Indeed, Bartholomew et al found that survival of allogeneic skin transplants was prolonged when combined with BM-MSC.…”
Section: Multipotent Progenitor Cellsmentioning
confidence: 99%